2022
DOI: 10.1093/ckj/sfac249
|View full text |Cite
|
Sign up to set email alerts
|

Impact of immunosuppressive treatment and type of SARS-CoV-2 vaccine on antibody levels after three vaccinations in patients with chronic kidney disease or kidney replacement therapy

Abstract: Background Patients with chronic kidney disease or kidney replacement therapy demonstrate lower antibody levels after SARS-CoV-2 vaccination compared to healthy controls. In a prospective cohort, we analysed the impact of immunosuppressive treatment and type of vaccine on antibody levels after three SARS-CoV-2 vaccinations. Methods Control subjects (n = 186), patients with CKD G4/5 (n = 400), dialysis patients (n = 480) and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Similar to other reports with ChAdOx1 and mRNA vaccines [ 44 , 50 ], we observed that even after a third dose of BNT162b2 a proportion of KT patients do not have neutralizing antibodies, especially patients under mycophenolic acid or sodium mycophenolate treatments, consistent with previous reports showing decreased humoral responses in patients receiving mycophenolate [ 33 , 34 , 51 ]. It has been shown that mycophenolic acid significantly inhibits proliferation and differentiation of primary human B cells, impairing immunoglobulin secretion of activated but not terminally differentiated B cells [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to other reports with ChAdOx1 and mRNA vaccines [ 44 , 50 ], we observed that even after a third dose of BNT162b2 a proportion of KT patients do not have neutralizing antibodies, especially patients under mycophenolic acid or sodium mycophenolate treatments, consistent with previous reports showing decreased humoral responses in patients receiving mycophenolate [ 33 , 34 , 51 ]. It has been shown that mycophenolic acid significantly inhibits proliferation and differentiation of primary human B cells, impairing immunoglobulin secretion of activated but not terminally differentiated B cells [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…The third vaccine dose given more than three months after the primary vaccination has been shown in patients with RD to increase the RBD-IgG level, NAb titer against wt/Omicron and T cell response significantly, and compared to healthy controls lower or similar response levels have been reported [37, 39]. In patients with CKD, the third dose has been demonstrated to increase the antibody levels, proportion of participants with NAbs and NAb titer levels and T cell responses [4043] and seroconversion has been observed in patients who did not respond after two vaccine doses [34, 44]. However, in kidney transplant recipients the rates of response have remained suboptimal [41].…”
Section: Discussionmentioning
confidence: 86%
“…We determined the lower limit of a normal antibody response to vaccination as the 5 th percentile of the antibody concentrations; 398 and 716 BAU/ml for RBD-IgG and SFL-IgG, respectively. All controls had NAb against WT and Omicron BA.1; with GMTs 404 (95% CI 269-608) and 26 (95% CI [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], respectively (Figure 3).…”
Section: Antibody Levels After the 3rd Dose In Healthy Controlsmentioning
confidence: 99%
“…CKD and RD associated with immunosuppressive therapy have also, in previous studies, shown to impact immune responses to COVID-19 vaccinations. Previous studies have shown overall seroconversion rates being as high as in healthy controls after the primary vaccination [ 34 , 35 , 36 ] but with significantly lower mean RBD-IgG antibody levels, NAb antibody titers (against wt), and lower T-cell responses compared to healthy subjects [ 6 , 34 , 37 , 38 , 39 ]. The third vaccine dose given more than three months after the primary vaccination has been shown in patients with RD to increase the RBD-IgG level, NAb titer against wt/Omicron and T cell response significantly, and compared to healthy controls lower or similar response levels have been reported [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%